Izzivi prenove spletišča Medicinske fakultete v Ljubljani - Leskošek, Branimir (Informatica Medica Slovenica, 2008)
The old website of Faculty of Medicine (FM) in Ljubljana was established in 1993 and it doesn't provide the efficient and easy updating according to today's standards. Approximately two years ago the project of website renewal was started. The challenges were not only technical but mainly organizational to the extent that was not foreseen at the beginning. The main challenge was how to make possible for almost 50 organizational units of FM to adopt the new, electronic, way of content publishing and to distribute the publishing responsibilities more clearly. Besides the fresh design the new website offersthe visitors an easy access to up-to-date content and allows local editors situated at the organizational units to publish information using the content management system. In the future the development will be focused towards the personalization of website services. Any response is welcome at splet@mf.uni-lj.si.
Keywords: Computer Communication Networks; Faculty, Medical; Fakulteta medicinska; Medicinska fakulteta (Ljubljana); Računalniške mreže; računalništvo